(untitled) (Journal of Education and Development, 2022)
Teacher collaboration is of great significance to improve the professional ability and development of teachers. This study shows that the traditional path of teachers’ professional development has gradually lagged behind the pace of the development of the times, and the new path of teachers’ professional development with teachers’ collaboration as the core is attracting much attention. This study examines and reflects on the hot topics in the concept and practice of teacher collaboration from the aspects of the theoretical implication, manifestation and implementation dilemma of teacher collaboration. In fact, under the development concept of teacher collaboration, there are many implementation difficulties. Providing time guarantee for teacher collaboration, guiding teachers to correctly understand teacher collaboration and balancing the limits of teacher autonomy and collaboration are very important to promote teacher collaboration.